2016
DOI: 10.1002/14651858.cd007451.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure lowering efficacy of beta-1 selective beta blockers for primary hypertension

Abstract: This review provides low quality evidence that in people with mild to moderate hypertension, beta-1 selective blockers lowered BP by an average of -10/-8 mmHg and reduced heart rate by 11 beats per minute as compared to placebo. The effect of beta-1 blockers at peak hours, -12/-9 mmHg, was greater than the reduction at trough hours, -8/-7 mmHg. Beta-1 selective blockers lowered BP by a greater magnitude than dual receptor beta-blockers and partial agonist beta-blockers, lowered BP similarly to nonselective bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 71 publications
0
8
0
2
Order By: Relevance
“…Decreasing PR leads to a compensatory increase in cardiac output and elevated systolic BP; prolonged diastolic interval leads to decreasing diastolic BP, which results in widened PP. In the Cochrane Database of Systematic Reviews, β‐blockers reduced BP (systolic BP: −10 mm Hg, diastolic BP: −8 mm Hg) and lowered PR (−11 bpm) but did not reduce PP . The elevated sympathetic nervous activity contributes to accelerated arterial stiffening .…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing PR leads to a compensatory increase in cardiac output and elevated systolic BP; prolonged diastolic interval leads to decreasing diastolic BP, which results in widened PP. In the Cochrane Database of Systematic Reviews, β‐blockers reduced BP (systolic BP: −10 mm Hg, diastolic BP: −8 mm Hg) and lowered PR (−11 bpm) but did not reduce PP . The elevated sympathetic nervous activity contributes to accelerated arterial stiffening .…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed, with appropriate controls, that mean arterial blood pressure decreased in an amount similar to reported values for beta-adrenergic antagonists that are also clinically effective to not only reduce blood pressure, and in humans can cause fatigue (16). In a review of 56 randomized controlled trials examining the blood pressure lowering effects of beta-1 selective blockers, the average reduction in blood pressure was 10 and 8 mmHg in systolic and diastolic blood pressure, respectively, in patients with mild to moderate hypertension (17). An associated side effect of the beta-blocker propranolol is fatigue (18).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies aimed at clarifying the effects of carvedilol and nebivolol would be valuable given that recent meta-analyses suggested that BP lowering by combined β/α-receptor blockers (ie, carvedilol) was less effective than by β 1 -selective blockers (ie, nebivolol). 49,50 As the most frequently used and preferred source of education by physicians in this study, CME modules and peer-reviewed publications may provide greater benefit than other initiatives for accessible and consistent educational efforts.…”
Section: Discussionmentioning
confidence: 99%